(untitled) (Medical Forum Monthly, 2023)
Objective: To find out the epidemiology and pattern of colonic diverticular disease in patients undergoing lower Gastrointestinal (GI) Endoscopy. Study Design: Descriptive observational study Place and Duration of Study: This study was conducted at the Department of Gastroenterology at Hayatabad Medical Complex Peshawar from 12th December 2022 till 25th March 2023. Materials and Methods: The study was carried out after approval from the hospital's ethical committee. Informed consent was obtained from all patients who were included in the study. Patients undergoing screening, diagnostic and therapeutic colonoscopy aged 40 to 80 years were enrolled. Diverticular disease was confirmed by the presence of out-pouching of colonic mucosa through its wall, forming a sac-like structure. The number and location of the diverticula were noted. Results: A total of 184 patients were enrolled. Diverticular disease was observed in 28 patients (15.2%). The mean age of the patients was 59.23±11.873 years. Male to female ratio was 1.7:1. Sixty-six participants (35.9%) were 61-70 years old. A statistically significant association was observed between age and diverticulosis. The likelihood of the disease increases with advancing age. The total number of male participants was 116 (63.0%), of which 23 patients (19.8%) had the disease. Left-sided was most affected in 13 patients (46.2%). Multiple diverticula were found in 19 patients (67.8%). Conclusion: The current study demonstrates that colonic diverticulosis is less frequent (15.2%) in our setup. Among patients with diverticulosis in our setup, it is more prevalent in elderly males, and multiple diverticula affecting the left-sided colon is the most frequent colonoscopic finding in such cases.